The Effect of Using Plank Exercises on Developing the Skill Performance of Reception and Setting in Volleyball - Al-Zubaidi, Ali Hameed Ali (Pubmedia Jurnal Pendidikan Olahraga, 2025)
This study aimed to measure the effect of Plank Exercises on improving the skills of Reception and Setting among volleyball players. An experimental approach was applied to a sample of 12 players, divided into two groups. The experimental group underwent an 8-week progressive-intensity Plank exercise program (3 sessions per week), while the control group continued with their traditional training. Results showed a statistically significant improvement (<0.05p<0.05) in reception accuracy and setting stability for the experimental group compared to the control group. The study confirms the importance of Core Stability training in enhancing the technical performance of fundamental volleyball skills. It concluded that the Plank exercise program had a statistically significant positive effect on improving the accuracy of reception and setting skills among the experimental group players. The improvement in both skills was substantially greater and statistically significant for the experimental group compared to the control group, which did not undergo the Plank program. The study recommended systematically and progressively incorporating various Plank exercises (front, side, and advanced variations) into volleyball training programs at all levels, and designing specialized Plank programs focusing on aspects most impactful for specific skills (e.g., increasing side plank difficulty to improve reception of deflected balls).